Artificial noise aided secure beamforming for multi-antenna relay systems - Li-jian ZHANG; Liang JIN; Lu LIU; Wen-yu LUO (Tongxin xuebao, 2014)
In the amplify-and-forward (AF) relay systems，the confidential information forwarded by the relay can be intercepted by the eavesdroppers.For guaranteeing the secure communications，an artificial noise aided secure beamforming method is proposed.The goal is to maximize the secrecy rate of the system by jointly designing the beamforming matrix and the artificial noise (AN) covariance matrix at the relay subject to the total power and the per-antenna power constraints.This non-convex secrecy rate maximization (SRM) problem can be recast as a two-level optimization problem.The outer part can be solved by performing a one-dimensional search，and the inner part can be handled by the semidefinite relaxation (SDR) technique and interior-point methods.It is shown that there always exists a rank-one optimal solution for the SDR problem，i.e.，the relaxation is tight to the original problem.Simulation results demonstrate that the proposed method can improve the security performance of the system significantly.